PENINGKATAN KEMAMPUAN MEMBACA ANAK DI NEGERI PILIANA KABUPATEN MALUKU TENGAH - setiyawan, anang; Zainuddin Akbar, Muhammad (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
Reading skills are essential competencies that children must develop prior to advancing to higher educational levels. Children in Negeri Piliana encounter difficulties in acquiring reading skills due to inadequate educational facilities and infrastructure. The Gopala Valentara Student Activity Unit, Faculty of Law, Universitas Sebelas Maret, implemented a community service initiative to enhance literacy among elementary school children in Negeri Piliana. This program utilised effective pedagogical methods to improve children's reading abilities. The program's results demonstrated substantial enhancements in literacy instruction techniques, rendering them more engaging for educators, alongside an elevation in literacy rates among students at SD Kristen Piliana.